Efektivitas Penugasan Berbasis e-Learning terhadap Implementasi Kurikulum Pendidikan Agama Islam pada Pembelajaran Akidah Akhlak di Madrasah Tsanawiyah - Fahmi Saenong Amiluddin, Zul; Ahdar; Buhaerah (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to analyze the effectiveness of e-learning–based assignments in supporting the implementation of the Islamic Education Curriculum within the Aqidah Akhlak subject at the madrasah level. Using a descriptive quantitative design, the research involved 120 students who completed a Likert-scale questionnaire measuring key indicators of learning effectiveness, including accessibility of digital platforms, learning independence, student engagement, and the alignment of digital tasks with curriculum objectives. Data were analyzed through descriptive statistics to obtain mean scores, percentages, and indicator distributions. The findings show that e-learning–based assignments are categorized as highly effective, with an overall average score of 90. Students reported increased flexibility, motivation, independence, and meaningful learning experiences through the use of videos, quizzes, discussion forums, and structured digital tasks. The strategy also strengthened character formation, collaboration, and authentic assessment. Teachers were able to optimize digital media to enhance interaction and instructional quality, while schools supported implementation through relevant technological facilities. These results confirm that digital task strategies play a significant role in realizing curriculum principles and achieving learning objectives, making them highly relevant to contemporary educational demands.